Essop Pahad - Letlhokwa Mpedi (The Thinker)
Whilst many will speak today of the historic and invaluable contributions of Essop Pahad to our country’s liberation struggle and at the dawn of democracy, it is often forgotten that this came at great pain for him to live a life in exile, isolated from family and friends. Such was the often silent struggle that happened parallel to the struggle for freedom. Though this was an immensely politically active time for him, it was also incredibly taxing. It was in this time that Essop clung to the promise of a free and democratic South Africa. As the Greek tragedian Aeschylus once said: ‘I know how men in exile feed on dreams.’ So desperate was his dream for a better tomorrow that he worked tirelessly with members of the international community to bring attention to the plight of those he left behind. Throughout his life, he continued to cling onto this dream as he fought for justice and equity long beyond the advent of democracy. He once said: ‘Our march to a better life requires that each and every South African should put shoulders to the wheel – all of us as partners in transforming ours into a society that cares. We must know our rights and exercise them, in the same measure as we take on our collective responsibility to build South Africa into a nation of our dreams.’